Comprehensive approach in rendering assistance to persons affecting drug addiction: experience of the Republic of Belarus and the Austrian Republic - Gusentsov, Alexandr O. (Journal of the Belarusian State University. Law, 2019)
Based on the study of statistical data, an analysis of negative trends in the consumption of narcotic drugs in the world and in the Republic of Belarus was conducted. The main results of a fact-finding visit to the United Nations Office on Drugs and Crime (Vienna) are presented: epidemic situation and the relationship between HIV and drug abuse in the Republic of Belarus, the main provisions and ways of implementing Decree No. 6 of the President of the Republic of Belarus on 28 December 2014 «Urgent measures to counter illegal drug trafficking», prospects for cooperation between the Ministry of Internal Affairs of the Republic of Belarus and public organizations on these issues were presented to the international community; modern approaches to the provision of comprehensive assistance and treatment of drug dependence in the Republic of Austria, the principles of organizing the work of the Center for Assistance to People Suffering from Drug Addiction were studied, and recommendations for the possibility of applying effective strategies for helping drug dependent persons in the Republic of Belarus were worked out.